Sosialisasi Pijat Oketani Sebagai Upaya Pencegahan Bendungan Asi - Heryani, Sri; Fatimah, Siti; Rohmah, Siti; Heriyanti, Silvia Widyani (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Breast milk duct obstruction, or bendungan ASI, is a common challenge experienced by breastfeeding mothers and can lead to complications such as mastitis if not addressed properly. Pijat Oketani is a specific massage technique known to facilitate breast milk flow and prevent duct blockage. Objective: The purpose of this community service activity was to increase mothers’ knowledge and skills in applying the Oketani massage technique as a non-pharmacological effort to prevent breast milk duct obstruction. Method: The activity was conducted on Wednesday, April 18, 2025, at the Puskesmas Sadananya service area, involving 25 breastfeeding mothers with infants aged 0–6 months. The method included a pre-test, interactive counseling, demonstration, hands-on practice, and post-test. Quantitative evaluation was conducted using a questionnaire and observation checklist. Result: There was a significant increase in participants’ knowledge, with average post-test scores rising from 56% to 88%. Additionally, 76% of participants were able to correctly perform the Oketani massage during the practice session. Participants reported feeling more confident and equipped to manage breastfeeding challenges independently. Conclusion: The Oketani massage technique can be effectively introduced through community-based education and hands-on training. This program has proven successful in empowering mothers to prevent breast milk duct obstruction and is recommended for wider implementation in maternal and child health promotion.